Effect of the Magnetic Field on the Characteristics of the Dusty Plasma FeO by Using the Direct Current System - Ahmed, Ala' F.; Karim, Noorhan; Abbas , Qusay A. (Iraqi Journal of Science, 2021)
In the present work, the effect of isolated dust particles (FeO) with radius of the grain 0.1μm - 0.5μm of main plasma characteristics are investigated experimentally in direct current system by using magnetic field. The present of dust particle in the air plasma did effect on Paschen minimum and on the plasma properties in low pressure region. The effect of dust particles on discharge voltage, discharge current, plasma potential, floating potential, electron density, electron temperature and Debye length was investigation by using magnetic field. The measurements of parameters are taken by four cylindrical Langmuir probes. The results show the present of dust causes decreasing in discharge voltage with increase pressure while the discharge current was increased with increasing pressure. The floating potential and plasma potential of probe becomes more negatively. The electron density is increases in the present of dust particle which lead to decreases the electron temperature and Debye length.